14 The role of TILRR in vascular cell inflammation and development of atherosclerosis. Issue 20 (23rd September 2011) - Neilan, M; Boyle, J; Lawrie, A; Francis, S; Haskard, D; Qwarnstrom, E
Abstract : Inflammatory responses are induced by members of the Toll-like and Interleukin-1 receptor family. We have identified an IL-1RI (interleukin-1 receptor type I) co-receptor, TILRR, (toll-like and IL-1 receptor regulator), which associates with the signalling receptor and potentiates activation of NF-kB and inflammatory responses.1 Earlier studies have confirmed expression and function of TILRR in both inflammatory and vascular cells. More recent experiments have demonstrated a pronounced increase in TILRR expression in the atherosclerotic plaque using mouse models (ApoE−/− and LDLR−/−). The current studies focus on determining the role of TILRR in development of atherosclerosis, specifically in relation to its impact on IL-1-induced responses. Immuno-histochemical studies have demonstrated the presence of TILRR in sections of vascular lesions from human samples, correlating with areas of IL-1RI activity. In experiments using ApoE/IL-1RI double knockouts, the high fat diet had only minor impact on the level of TILRR expression in vascular tissue. We have confirmed specificity of the co-receptor to IL-RI by demonstrating that other receptor systems controlling vascular inflammation, such as TNFR, are insensitive to TILRR expression over a range of ligand concentrations. Ongoing studies use custom anti-TILRR antibodies to test effects of blocking TILRR association with IL-1RI on development of atherosclerosis. Antibodies are injected into fat-fed ApoE−/− mice, and plaque formation determined using computer based imaging and semi-quantitative scoring.